Growth and quality of lisianthus [Eustoma grandiflorum (Shinn.)] cultivated in rice husk substrates in troughs with leaching recirculation - Höhn, Daniela; Peil, Roberta Marins Nogueira; Marchi, Priscila Monalisa; Grolli, Paulo Roberto; Perin, Lais; Rosa, Douglas Schulz Bergmann da (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2019)
This study aimed to evaluate the growth and quality of lisianthus cultivated in different rice husk substrates. The evaluated substrates were: carbonized rice husk (CRH; 100%); raw rice husk (RRH; 100%); CRH (70%) + S10 Beifort® commercial organic compost (30%); and RRH (70%) + S10 Beifort® commercial organic compost (30%). Plant dry mass (DM) production and partitioning, plant leaf area and shoot/root DM ratio were analyzed. Quality parameters of the flower stems were also evaluated (length; diameter and number of flowers and buds). The RRH substrate at 100% reduced plant growth and prevented flower development. This modified dry mass partitioning among the plant organs. The substrates RRH + S10 and CRH provided quality flower stems. Thus, both substrates can be used to produce cut lisianthus flowers in recirculating nutrient systems. However, the RRH + S10 substrate stood out because it increased plant growth. This result is ascribed to the improvement of the physical and chemical properties of substrate RRH + S10 as a result of the presence of both the organic compost, which benefited the water holding capacity, and the RRH, which guaranteed high porosity to the substrate.